An ER clamp for endosome fission. (12th December 2014) - Raiborg, Camilla; Stenmark, Harald
<x xml:space="preserve">Abstract</x> Endosomes are known to undergo budding and fission reactions that separate regions destined for lysosomal degradation from carriers to be recycled to the plasma membrane. A recent paper (Rowland et al, 2014) shows that contact sites between endosomes and the endoplasmic reticulum (ER) define the position and timing for fission. This uncovers an unanticipated role for the ER in controlling endosomal sorting and maturation.